Discriminating complicated from uncomplicated appendicitis by ultrasound imaging, computed tomography or magnetic resonance imaging: systematic review and meta-analysis of diagnostic accuracy - Bom, W J (BJS Open, 2020)
BACKGROUND: Discriminating complicated from uncomplicated appendicitis is crucial. Patients with suspected complicated appendicitis are best treated by emergency surgery, whereas those with uncomplicated appendicitis may be treated with antibiotics alone. This study aimed to obtain summary estimates of the accuracy of ultrasound imaging, CT and MRI in discriminating complicated from uncomplicated appendicitis METHODS: A systematic literature review was conducted by an electronic search in PubMed, Embase and the Cochrane Library for studies describing the diagnostic accuracy of complicated versus uncomplicated appendicitis. Studies were included if the population comprised adults, and surgery or pathology was used as a reference standard. Risk of bias and applicability were assessed with QUADAS-2. Bivariable logitnormal random-effect models were used to estimate mean sensitivity and specificity. RESULTS: Two studies reporting on ultrasound imaging, 11 studies on CT, one on MRI, and one on ultrasonography with conditional CT were included. Summary estimates for sensitivity and specificity in detecting complicated appendicitis could be calculated only for CT, because of lack of data for the other imaging modalities. For CT, mean sensitivity was 78 (95 per cent c.i. 64 to 88) per cent, and mean specificity was 91 (85 to 99) per cent. At a median prevalence of 25 per cent, the positive predictive value of CT for complicated appendicitis would be 74 per cent and its negative predictive value 93 per cent. CONCLUSION: Ultrasound imaging, CT and MRI have limitations in discriminating between complicated and uncomplicated appendicitis. Although CT has far from perfect sensitivity, its negative predictive value for complicated appendicitis is high.